Kant'ın İdealizmi Reddi - Küçükparmak, Aykut (My University, 2017)
Bilen özneden bağımsız ontolojik bir gerçekliğin var olup olmadığı konusu felsefenin önemli problem alanlarından biridir. Bu sorun Kant'ın eleştirel felsefesinde de önemli bir yere sahiptir. Bu çerçevede Kant, idealizmi problematik ve dogmatik idealizm olarak ikiye ayırır. O, Descartes'e atfettiği problematik idealizmle mekAnsal objelerin varlığının şüpheli olduğu iddiasını kast eder. Diğer taraftan dogmatik idealizm ile mekAnsal objelerin varlığının imkAnsız olduğunu dile getiren Berkeleyci idealizmi kast eder. Kant idealizmin bu iki formuna karşı transendental idealizm tezi üzerinden dış dünyanın varlığını ve bunu bilmenin mümkün olduğunu göstermeye çalışır. Kant'ın bu bağlamda öne sürdüğü argümanlar hem idealizm tartışmaları hem de eleştirel felsefenin anlaşılması açısından önemli bir yere sahiptir.

Topic of whether there is ontological reality independent from the subject who knows is one of the important problem areas of philosophy. This problem also has an important place in Kant's philosophy. In this framework, Kant distinguishes between problematic and dogmatic idealism. By problematic idealism which he ascribes to Descartes he means to the hypothesis that existence of spatial objects is doubtful. On the other hand, by dogmatic idealism which is attributed to Berkeley he means to claim that existence of spatial object is an impossibility. Against these two forms of idealism Kant tries to show existence of spatial object and the possibility to know them through transcendental idealism. In this context, arguments which Kant put forward have an important place for understanding both idealism discussions and the critical philosophy.
Kant's Refutation of Idealism